Щит небесный: рассказы / рисунки Н. Зыкиной - Зыкина Н. (Православная детская библиотека, 2001)
Экземпляры: ф.14 (20250218) / Инвентарный номер: 65568 / Цена: / Сис.шифр: 84(2=411.2)-4 / Авт.знак: Щ 88 / ГРНТИ: 17.82.93 / ББК: 84(2=411.2)-44